Visually induced inhibition of return affects the integration of auditory and visual information - Van der Stoep, N; Van der Stigchel, S; Nijboer, T; Spence, C (SAGE Publications, 2016)
Multisensory integration (MSI) and exogenous spatial attention can both speedup responses to perceptual events. Recently, it has been shown that audiovisual integration at exogenously attended locations is reduced relative to unattended locations. This effect was observed at short cue-target intervals (200-250 ms). At longer intervals, however, the initial benefits of exogenous shifts of spatial attention at the cued location are often replaced by response time (RT) costs (also known as Inhibition of Return, IOR). Given these opposing cueing effects at shorter versus longer intervals, we decided to investigate whether MSI would also be affected by IOR. Uninformative exogenous visual spatial cues were presented between 350 and 450 ms prior to the onset of auditory, visual, and audiovisual targets. As expected, IOR was observed for visual targets (invalid cue RT < valid cue RT). For auditory and audiovisual targets, neither IOR nor any spatial cueing effects were observed. The amount of relative multisensory response enhancement and race model inequality violation was larger for uncued as compared with cued locations indicating that IOR reduces MSI. The results are discussed in the context of changes in unisensory signal strength at cued as compared with uncued locations.